O estado atual das intituiç\~oes financeiras públicas para o desenvolvimento na América Latina: Uma análise exploratória - Victor Leonardo de Araujo; Murilo José de Souza Pires; Márcio Francisco da Silva; Diego Afonso de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This article aims to reflect on recent transformations happened in development financial institutions (DFI) in Latin America. To this end, we selected DFI that act in the major economies in Latin America, except the Brazil. The work give preference to public institutions that had activities in the productive sector, excluding those that are solely focused on real estate financing. In general, it was found on investigation that the major changes experienced by many DFIs on the continent are related to changes in second floor institutions. Regarding the funding structure, we verified a reduction of resources from their governments (central banks and treasures) and increase in private resources (deposits and capital markets) or foreign resources through official agencies (like World Bank and Andean Development Corporation). Despite the lack of statistical data for DFIs in the region, we verified that the credit operations for many of these have the shortest term of that that what would be expected for this kind of institution. Notwithstanding, the historical function of to finance industry, agriculture and infrastructure was been preserved. Foreign trade and small and medium enterprises are emerging as important agenda to the DFI in the region.
Keywords: N26; 330; Entwicklungsbank; Entwicklung; Lateinamerika